Study on a Moisture Ratio Curve Model for Refractance Window Drying Based on a D-Optimal Mixture Design - Jingyu He; Weidong Song; Jianqiang Li; Tianhang Ding; Jian Guan; Jinji Wu; Jiaoling Wang (Journal of Food Quality)
Refractance window (RW) drying is a new thin-layer drying technology that can control well the heating temperature to effectively reduce the loss of heat-sensitive substances. Here, an experiment on tomato pulp drying was carried out to study the drying characteristics of RW drying based on a D-optimal mixture design. The fitting of the classical model of thin-layer drying was studied, and SAS and 1stOpt calculation software were used to analyze the test data. The result showed that the RW drying equipment could dry 8 mm of tomato pulp in 120 min, and the maximum drying speed could reach 0.40 g/(g·min). Based on an effective diffusion coefficient under different conditions, the activation energy was 27.35 kJ/mol at an air speed of 3 m/s. When comparing the fitting of the moisture ratio curve in four classic thin-layer drying models, it was found that the R-square value of the modified Page model was 0.9960, which had better fitting properties. Then, the polynomial fitting model of thin-layer drying reflects the regression relationship between the coefficient of the classic model and drying conditions including temperature, wind speed, and time. After comparison with the classic model and validation experiment, the results showed that there is no significant difference between the polynomial fitting model and the validations under a confidence level of 0.95, which could well predict the change in the water content ratio over time under different conditions.